Theoretical Research on Product Quality Evaluation Under the Background of Large Data Based on Gray System——Using Midea Refrigerator as a Case Study - Niu, Yuxiang (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
In this paper, by combining the gray system theory and analytic hierarchy process to process product big data and evaluate product quality to determine the standard, through the questionnaire survey and expert interviews to determine 16 product quality indicators. This paper adds the relevant indicators of ecological quality “degree of pollution to the environment and reasonable use of resources” to establish and improve the product quality evaluation system. Taking the refrigerator of Midea as an example, the internal quality, appearance quality, economic quality, market quality and ecology of the product From the perspective of quality, the quality of the selected three models of refrigerators can be evaluated, and the quality of refrigerators under the unified standard evaluation system can be reflected intuitively through quantitative methods.